Voices countering whiteness in the Israeli Arab classroom. Issue 1 (2nd January 2019) - Hayik, Rawia
ABSTRACT: Situated within the Israeli context and the country's massive investment in the Jewish majority on the expense of the Arab minority, this article describes an English teacher's attempt to address issues of whiteness with a group of four Israeli-Arab ninth-grade students. Using Rosa Parks' story as a springboard for broaching these issues, the minority students were invited to reflect on and discuss the relevance of the story to their reality. Students' discussion was videotaped and later transcribed and analyzed to scrutinize emerging themes. The analysis shed light on significant differences in students' viewpoints and identities, where two of them condemned the establishment's discriminatory acts towards the Arab minority while the other two refused to acknowledge facts attesting to the majority's privilege and power. The significance of the study lies in providing a stage for often-silenced minority students to voice their views on issues of whiteness in the Israeli reality.